2019
DOI: 10.35940/ijrte.d8472.118419
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Low-Cost Hip Implant using Direct Metal Laser Sintering Technique

Abstract: Total hip replacement (THR) is the most popular surgery been performed in orthopedic surgery due to the inclination of musculoskeletal disorder and the aging population worldwide. However, the implant’s cost-burdened the patient, especially in the ASEAN region. The main objective of this study was to fabricate the low-cost hip implant using direct laser metal sintering (DMLS). The framework starts with the three dimensional of hip anthropometric datasets from computed tomography scanner, followed with the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…DMLS and EBM have been used in recent years for the development of customized hip implants. In fact, previous studies developed by Cronskar et al 13 and Baharuddin et al 14 have shown the feasibility of manufacturing Ti-6Al-4V femoral implants using DMLS and EBM. Customized implants for patients with a specific clinical condition and anatomy are currently a major need to minimize the risk and complications associated with the use of current predefined commercial hip implants.…”
Section: Introductionmentioning
confidence: 99%
“…DMLS and EBM have been used in recent years for the development of customized hip implants. In fact, previous studies developed by Cronskar et al 13 and Baharuddin et al 14 have shown the feasibility of manufacturing Ti-6Al-4V femoral implants using DMLS and EBM. Customized implants for patients with a specific clinical condition and anatomy are currently a major need to minimize the risk and complications associated with the use of current predefined commercial hip implants.…”
Section: Introductionmentioning
confidence: 99%